Complete chloroplast genome of Prunus fruticosa and its implications for the phylogenetic position within Prunus sensulato (Rosaceae) - Yu-Xin Yang; Mi-Hui Tian; Xin-Hong Liu; Yue-ling Li; Zhong-Shuai Sun (Mitochondrial DNA. Part B. Resources, 2020)
Prunus fruticosa is a wild species of Prunus distributed across the central Eurasia. Here, we reported the complete chloroplast (cp) genome of P. fruticosa (GenBank accession number: MT916286). The cp genome was 158,217 bp long, with a large single-copy region (LSC) of 86,322 bp and a small single-copy region (SSC) of 19,153 bp separated by a pair of inverted repeats (IRs) of 26,371 bp. It encodes 129 genes, including 84 protein-coding genes, 37 tRNA genes, and 8 ribosomal RNA genes. We also reconstructed the phylogeny of Prunus sensu lato using maximum likelihood (ML) method, including our data and previously reported cp genomes of related taxa. The phylogenetic analysis indicated that P. fruticosa is closely related with Prunus avium.